Leucoraja elaineae sp. nov., a new rough skate (Rajiformes: Rajidae) from the Western Indian Ocean - Ebert, David A.; Leslie, Robin W. (Zootaxa, 2019)
A new species of the genus Leucoraja is described from off Kenya in the Western Indian Ocean (WIO). The new species was collected during a survey of the R/V Fridtiof Nansen. Leucoraja elaineae sp. n. is the third species in the genus found to occur in the WIO, and the only species in the genus Leucoraja known exclusively from this region. Its closest geographic congener L. wallacei, occurring from Namibia to southern Mozambique, can be separated by a combination of morphological and meristic characters including an elongated, pronounced snout (L. elaineae sp. n.) vs a short, blunt snout (L. wallacei), higher predorsal vertebral (107 vs 64-74) and pectoral fin radial counts (77 vs 61-64), a dorsal surface pattern consisting of a single ocelli at the midbase of each pectoral fin, paired small white spots, and no banding or crossbars on its tail vs numerous rosettes and whorls, no prominent ocelli at the pectoral fin bases, and 3-4 tail bands. The only other WIO Leucoraja species in the genus, L. compagnoi is known only from South Africa and has a short, blunt snout, a lower upper tooth count (38 vs 57 in L. elaineae sp. n.), a plain dorsal disc color with no markings and distinct bands on its tail. All other members of the genus occur in the North Atlantic, except one species that occurs in the eastern Central Atlantic and one in the eastern Indian Ocean.